Refocusing on Reallocation of Regional Shopping During the Pandemic Covid-19 in the Government of North Maluku Province - Salis Ariza Abdi Hidayat; Abdul Hadi Sirait; Suwito (Jurnal Economic Resource, 2022)
Refocusing and Reallocating Regional Expenditures During the COVID-19 Pandemic in the North Maluku Provincial Government. This study aims to describe the management of refocusing activities and reallocation of the regional budget of the North Maluku Provincial Government for Fiscal Year 2020. The research method used is descriptive qualitative research with a case study approach. The North Maluku Provincial Government rationalized the regional expenditure budget to obtain funds for handling COVID-19 in the form of refocusing regional spending on 17 SKPDs amounting to Rp. However, the expenditure rationalization value did not reach the percentage according to the provisions of the Minister of Home Affairs and the Minister of Finance. There are problems in implementing expenditures resulting from refocusing activities and reallocating budgets, including planning for the procurement of goods and services in the health sector, which is not appropriate, and the use of funds for activities that are not directly related to the handling of the COVID-19 pandemic. Accountability for spending from the results of refocusing activities and reallocating budgets shows that more use of funds is realized in the form of purchasing medical devices, providing honoraria, and official travel expenses.